Psychometric properties of the SPWB Psychological Well-being Scale of Carol d. Riff in secondary school students of the UGEL 02 - Díaz Gamarra, Patricia del Pilar (2020)
This research presents the Psychometric Properties of the Riff SPWB Psychological Well-being Scale in secondary students of UGEL 02. It was administered to a sample consisting of 1188 adolescents, chosen by a probabilistic sampling. The objective of the present investigation was to describe the psychometric properties of the Riff SPWB Psychological Well-being Scale in secondary students of UGEL 02. The scale was reduced from 34 to 12 items based on the item-test correlation ≥ .30, and the factor table ≥ .40. The relevance of the four-factor model to measure psychological well-being in adolescents was verified: Autonomy, Growth, Purpose and Self-acceptance. The internal consistency quantified with the Omega coefficient was 0.86 and for Alpha was 0.72, considered acceptable. Interpretation standards based on percentile ranks were developed.